Pemodelan Simulasi dalam Pengoptimalan Penjualan Plastik HD Menggunakan Metode Monte Carlo - Elvina Rahayu; Muhammad Thoriq; Sopi Sapriadi (Jurnal Informasi dan Teknologi, 2022)
Simulation modeling is used as a tool to see a picture of the company's condition in the future and as a forum for making a decision. Currently, sales are an important activity and a factor that must be considered in future planning. The purpose of sales is to bring profit or profit from products or services produced with good management. Simulation can help solve everyday problems such as existing problems, with simulation applications estimating the number of sales is very important. If someone can predict the number of sales, the cost of procurement and storage of goods can be minimized. From this, several parties can bring in profits as much as possible, and minimize losses. There are 18 sales sample data processed in this study, namely sales data from 2021 to 2022. Sales data is processed using the Monte Carlo method from January 2021 to June 2021 to predict results for July to December 2021. Then for July to December 2021 to predict the results for January to June 2022. The data is tested with various elements of probability using a random sample. A powerful numerical calculation tool by simulating statistical data, this simulation obtains accurate accuracy values ​​from the observable physical form of the system. Implementation of calculations will be developed using an application-based system that will be built with the JAVA programming language. The test results that have been obtained in the form of the average number of product requests and average income will be used as an estimate of sales (state estimate) that can assist in making decisions based on the information that has been obtained. The data obtained has an accuracy rate of up to 80%.